The crucial role of motorcycle-based ride-hailing among commuters: The case of Jakarta and Bandung metropolitan areas - Adiwan Fahlan Aritenang (Journal of Public Transportation, 2024)
In Indonesia, issues in the metropolitan transportation sector are considered severe. For instance, peripheral districts in the Jakarta metropolitan area (JMA), such as Bogor, Depok, Tangerang and Bekasi, contribute to the high mobility rate within the metropolitan area. This article examines the extent of motorcycle-based ride-hailing for commuting in the JMA and Bandung metropolitan areas (BMA). In particular, this study explores ride-hailing users’ characteristics—social, economic and spatial—and their proportion to the total commuter mobility in a metropolitan area. The study employed descriptive statistical models using commuter data in the JMA and BMA, respectively. Our results indicate that young and lower-income commuters are the dominant users of ride-hailing services. As motorcycle taxi services are relatively cheaper and accessible, young and lower-income commuters, including informal workers, prefer ride-hailing services. The study also suggests the impact of the intensification of inter-peri-urban mobilities of post-suburbanisation on the increasing demand for ride-hailing. In this sense, the study proposes that the long-overdue strengthening of metropolitan-scale governance is urgently required. It is also crucial for metropolitan governments to issue appropriate inter-district public transportation policies and engage in development.